Circuit modeling and analysis of microwave acoustic interaction with biological tissues - Zheng, Qian. (2013)
This report records the study and development of using microwave-based imaging for early tumor detection. Both microwave imaging(MWI) and microwave-induced thermoacoustic imaging(MTAI) are applied to provide high contrast performance with more safety and lower cost[6-8]. An equivalent circuit model can effectively model the microwave acoustic interaction with biological tissues using MWI and MTAI.